CHALLENGES FACED BY NURSES IN CARING FOR ELDERLY VICTIMS OF DOMESTIC VIOLENCE: A QUALITATIVE APPROACH - Sobral, Jordânia Paixão; Marinho, Marcella Lima; Rocha, Bruno Miranda da (Cogitare Enfermagem, 2023)
Objective: To describe the challenges faced by nurses in detecting and caring for elderly victims of domestic violence. Method: an exploratory, qualitative study carried out with 13 nurses from 13 Family Health Strategy Units in Boa Vista, Roraima, Brazil, with interviews conducted between March and July 2021, which were subjected to Bardin's content analysis. Results: Of those interviewed, 75% found no difficulties in detecting elderly people who had been abused. The interviewees refer the elderly to the Social Assistance Reference Center or to the competent bodies. Financial violence is prevalent. Conclusion: Detecting elderly people who have been abused depends not only on the professional, but also on the contribution of the victims, the community and the competent bodies. It was found that the participants did not have a formalized protocol for violence against the elderly, but only reported it and referred them to the relevant services.